Operationalising and explaining environmental policy styles - Tosun, Jale; Debus, Marc (The Routledge handbook of policy styles, 2021)
Sectoral policy styles exist but are difficult to operationalise. This chapter shows how one method of identifying and differentiating such styles is to examine the positions of political parties on environmental protection. Political parties represent key actors in almost all democratic political systems, and the leaders of parliamentary groups decide which issues are to be placed on the legislative agenda, which members of parliament are to give speeches on what issues, and how the group is going to vote on a given issue. We show for six Western European countries, originally covered by Richardson (1982), that the distances between the environmental policy positions of parties forming coalition governments fluctuate. At times, the distances are hardly noticeable, whereas at other times there is marked disagreement between the parties. We argue that the environmental policy style varies over time: it is more efficient, consensual, and anticipatory with small ideological distances, but becomes lengthy, drawn-out, contested, and reactive when government parties hold different stances on environmental protection.
Gesehen am 14.06.2023